Qatar's Clean Diplomacy Facing Regional Conflict - Alfredha Shinta Putri; Surwandono Surwandono (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
Qatar is one of the richest countries in the Middle East region. Qatar is able to supply the third largest gas to the world and become the third largest exporter of liquid natural gas. This paper is interested in analyzing the behavior of the Qatari government amid various conflicts and tensions in the Middle East region. Qatar tends to position itself as a mediator of conflict. The Qatari government believes that by being a mediator in this conflict it can be a neutral position.Qatari governance is based on the basic norm structure that is used as a policy platform, and articulates it openly, with integrity, and is measurable. This is known as clean diplomacy. Qatar manages the crisis by remaining consistent with its image as a guardian of regional peace and stability. The image of Qatar as an 'honest broker' country is able to increase Qatar's legitimacy in the international public arena. This paper builds on arguments based on secondary document data, and interprets the data with a qualitative approach to understanding Qatar's foreign policy behavior. The analysis showed that the choice of governance of Qatar's clean diplomacy proved effective in managing the foreign political pressure of neighboring countries in the form of not escalating conflict, and Qatar's political and economic stability.